Targeting metabolic peculiarities: a potentially novel therapeutic approach for KRAS-mutant lung cancer? - Abdel-Rahman, Omar (Journal of Thoracic Disease, 2016)
Lung cancer is a leading cause of cancer-related mortality particularly in its advanced stages (1). The search for more effective therapies to improve the outcome of advanced non-small cell lung cancer (NSCLC) patients is a real hardship for the cancer research community (2). Profound understanding of NSCLC pathobiology has facilitated largely the development of a more personalized style of therapy (3).